Digital Assessment of Acquired Alexia and Agraphia: On the Relevance of Written Discourse - Jaecks, Petra; Jonas, Kristina (Frontiers in Communication, 2022)
The digital revolution has created challenges as well as opportunities for people with acquired reading (= alexia) and writing (=agraphia) impairments. Although it is difficult to validly assess written discourse, it is imperative that people with alexia and agraphia (PwAA) receive reliable diagnostics for the following reasons: 1) discourse in written and oral forms is highly relevant to daily interaction and participation, but there are no established tests or diagnostic procedures to assess written discourse; 2) reliable diagnostic measures are a prerequisite for any language rehabilitation, especially for the complex skills needed for written discourse; and 3) the continuing trend in digitalization offers new opportunities for easily collecting and assessing written discourse via digital means. In our manuscript, we highlight the relevance of written discourse for social participation and in the digital world and argue that in order to improve social participation in general and digital participation in particular for PwAA, remote assessment of written discourse abilities can be the basis for speech and language therapy treatment focused on communicative abilities.